Phase 2 randomized controlled trial of intravenous or intraperitoneal paclitaxel plus mFOLFOX6 vs. mFOLFOX6 as first-line treatment of advanced gastric cancer - Zhao, Shen; Su, Liyu; Chen, Yigui; Li, Xiaofeng; Lin, Peicheng; Chen, Wujin; Fang, Wenzheng; Zhu, Jinfeng; Li, Hui; Ren, Liping; Liu, Jie; Hong, Yanni; et al. (Frontiers in Oncology, 2022)
Objective We conducted a phase 2 trial to compare the safety and efficacy of intravenous paclitaxel or intraperitoneal paclitaxel plus mFOLFOX6 vs. mFOLFOX6 in untreated advanced gastric cancer. Methods Participants with untreated advanced gastric cancer were randomly assigned (1:1:1) to: intravenous paclitaxel 135 mg/m2 or intraperitoneal paclitaxel 80 mg/m2 plus mFOLFOX6 omitting bolus fluorouracil; or mFOLFOX6 (oxaliplatin 85 mg/m2, leucovorin 400 mg/m2, fluorouracil 400 mg/m2 bolus, fluorouracil 2,400 mg/m2 46-h continuous infusion). Treatment was every 14 days for up to 9 cycles followed by S-1 maintenance. The primary outcome was progression-free survival. Results Of 90 enrolled participants, 30 in the intravenous paclitaxel group, 29 in the intraperitoneal paclitaxel group, and 30 in the mFOLFOX6 group were included in the analyses. The median progression-free survival was 6.52, 5.83, and 4.55 months, respectively, for the intravenous paclitaxel group, intraperitoneal paclitaxel group, and mFOLFOX6 group. The hazard ratios were 0.56 (95% CI: 0.33–0.94; p = 0.026) and 0.56 (95% CI: 0.33–0.96; p = 0.037), respectively, for the intravenous paclitaxel group and the intraperitoneal paclitaxel group vs. the mFOLFOX6 group. The most common grade 3/4 adverse events for the intravenous paclitaxel group, intraperitoneal paclitaxel group, and mFOLFOX6 group, respectively, were neutropenia (30.0%, 34.5%, 33.3%), diarrhea (13.3%, 20.7%, 13.3%), and leukopenia (10.0%, 13.8%, 10.0%). No treatment-related death occurred. Conclusion The findings of this phase 2 trial suggest that adding intravenous paclitaxel or intraperitoneal paclitaxel to mFOLFOX6 for untreated advanced gastric cancer improved progression-free survival with manageable adverse events.